Biosynthetic gene profiling and genomic potential of the novel photosynthetic marine bacterium Roseibaca domitiana - Gattoni, Giuliano; Di Costanzo, Fabiana; de la Haba, Rafael R.; Fernández, Ana B.; Guerrero-Flores, Shaday; Selem-Mojica, Nelly; Ventosa, Antonio; Corral, Paulina (Frontiers in Microbiology, 2023)
Shifting the bioprospecting targets towards underexplored bacterial groups combined with genome mining studies are contributing to avoid the rediscovery of known compounds by revealing novel promising biosynthetic gene clusters (BGCs). With the aim to determine the biosynthetic potential of a novel marine bacterium, strain V10, isolated from the Domitian littoral in Italy, a comparative phylogenomic mining study was performed across related photosynthetic bacterial groups from an evolutionary perspective. Polyphasic and taxogenomic studies showed that this bacterium constitutes a new species, designated as Roseibaca domitiana sp. nov., a marine species of the genus Roseibaca, which so far is represented by a single valid described species name isolated from a hypersaline Antarctic lake. The genomic evolutionary study linked to BGC diversity revealed that there is a close relationship between the phylogenetic distance of the members of the photosynthetic genera Roseibaca, Roseinatronobacter and Rhodobaca and their BGC profile, whose conservation pattern allows discriminating between these genera. On the contrary, the rest of species related to Roseibaca domitiana exhibited an individual species pattern, unrelated to genome size or source of isolation. This study showed that photosynthetic strains possess a streamlined content of BGCs, of which 94.34% of the clusters with biotechnological interest (NRPS, PKS, RRE, and RiPP) are completely new. Among these, stands out T1PKS, exclusive of R. domitiana V10T, and RRE, highly conserved only in R. domitiana V10T and R. ekhonensis, both categories of BGCs involved in the synthesis of plant growth-promoting compounds and antitumoral compounds respectively. In all cases, with very low homology with already patented molecules. Our findings unveil the high biosynthetic potential of infrequent cultured bacterial groups, suggesting the need to redirect the attention to microbial minorities as a novel and vast source of bioactive compounds still to be exploited.